Improved PCA based Face Recognition using Feature based Classifier Ensemble - Nia, Fariba Fakhim Nasrollahi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Automatic face recognition has been a challenging problem in the field of image processing and has received a great attention over the last few decades because of its applications in different cases. Most of the face recognition systems employ single type of data, such as faces, to classify the unknown subject among many trained subjects. Multimodal systems are also available to improve the recognition performance by combining different types of data such as image and speech for the recognition of the subjects. In this thesis, an alternative approach is used where the given face data is used to automatically generate multiple sub feature data sets such as eyes, nose and mouth. Feature extraction is automatically performed by using rough features regions extracted from Viola-Jones face detector followed by Harris corner detector and Hough Transform for refinement. Automatically generated feature sets are used to train separate classifiers which would recognize a person from its respective feature. Given separate feature classifiers, standard data fusion techniques are used in the form of classifier assembling to improve the performance of the face recognition system. 10-Fold cross validation methodology is used to train and test the performance of the respective classifiers, where nine fold is used for training and one fold is used for testing. Principal component analysis (PCA) is employed as a data dimensionality reduction method in each classifier. Five different classifiers for right and left eyes, nose, mouth and face data sets are developed using PCA. The classifiers, of five different features are merged by different data fusion techniques such as Minimum Distance, Majority Voting, Maximum Probability, Sum and Product Rule. Overall, the proposed algorithm using the Minimum Distance improves the accuracy of state-of the art performance from 97.00% to 99.25% using ORL face database. Keywords: Face Recognition, Face Detection, Cross Validation, Viola-Jones Detection, Feature Extraction, Minimum Distance, Data Fusion, Classifier Ensemble.

ÖZ: Otomatik yüz tanıma, görüntü işleme alanında farklı uygulama olasılıklarından dolayı zorlu bir problem olarak yıllardır büyük bir ilgi çekmektedir. Yüz tanıma sistemlerinin bir çoğu yüz imgeleri gibi tek bir veri kaynağını kullanarak eğitilen şahıslar arasından bir kişiyi tanımaktadır. Multimodal sistemler de bu şahısların tanınması için görüntü ve konuşma gibi farklı veri türlerini birleştirerek tanıma performansını artırmak için kullanılabilmektedir. Bu tezde, eldeki yüz imgelerinin oluşturduğu veri setlerinden otomatik olarak gözler, burun ve ağız gibi birden çok öznitelik veri setleri çıkarılarak alternatif bir yaklaşım için altyapı oluşturulmaktadır. Viola-Jones yüz dedektörü kullanılarak çıkarılan kaba öznitelik bölgelerinden otomatik olarak Harris köşe dedektörü ve Hough dönüşümü ile ince ayar yapılarak otomatik öznitelik çıkarımı gerçekleştirilmektedir. Otomatik olarak oluşturulan öznitelik setleri ayrı ayrı sınıflandırıcıları eğitmek için kullanılmakta ve bir şahıs bu sınıflandırıcılar tarafından tanınabilmektedir. Elde edilen farklı sınıflandırıcılar standard veri füzyon teknikleri kullanılarak sınıflandırıcı topluluğu oluşturulmakta ve yüz tanıma sisteminin performansı arttırılmaktadır. 10-kat çapraz doğrulama yöntemi ile dokuz katı eğitim için, bir katı ise test için olmak üzere veriler, iki farklı gruba ayrılmakta ve bu yaklaşımla sınıflandırıcıların performansı ölçülmekedir. Ana bileşenler analizi (ABA) ile her bir sınıflandırıcının çok boyutlu uzaydaki veri boyutu düşük bir seviyeye indirgenmektedir. Gözler, burun, ağız ve yüz imge settleri ABA yöntemi kullanılarak beş farklı sınıflandırıcı oluşturulmaktadır. Beş farklı sınıflandırıcı, veri birleştirme yöntemleri kullanılarak birleştirilmekte ve bu amaçla en az uzaklık, çoklu oylama, eny üksek olasılık, toplam ve çarpım kuralları uygulanmaktadır. Sunuç olarak,önerilen yöntemlerden en az uzaklık kullanarak veri füzyonu gerçekleştiren yöntem literatürde ORL yüz veritabanı kullanan alternatif yöntemin performansını %97.00’den %99.25’e çıkarmaktadır. Anahtar Kelimeler: Yüz Tanıma, Yüz Sezimi, Capraz Validasyon, Viola-Jones Yüz Sezimi, Öznitelik Çıkarımı, Enaz Uzaklık, Veri Füzyonu, Sınıflandırıcı Topluluğu.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2015. Supervisor: Prof. Dr. Hasan Demirel.
Keywords: Electrical and Electronic Engineering; Computer vision - Face Recognition; Face Recognition; Cross Validation; Viola-Jones Detection; Feature Extraction; Data Fusion; Classifier Ensemble